4D-Space-Time Geometry & Cosmological Constant (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In this paper, 4-dimensional space-time geometry has been discussed. The smallness of the effective cosmological constant constitutes the most difficult problems involving cosmology. Recent observations of Type Ia supernovae and measurements of the cosmic microwave background suggest that the universe is in an accelerating expansion phase